Monitoring training and performance in athletes - McGuigan, M. (Human Kinetics, 2017)
The use of athlete and team training and performance monitoring systems has grown due to technology advances. Practitioners who work with athletes from high school to elite levels in a range of sports use these systems to observe athlete data, including exercise intensity, athletic fitness, and body responses. Monitoring Training and Performance in Athletes is a compilation of evidence-based guidelines and best practices of athlete monitoring for practitioners, who are increasingly being asked to implement monitoring systems and to collect, analyze, and interpret data that ultimately result in training adjustments to optimize performance.